Diseño e implementación de una red de datos para mejorar las comunicaciones de la empresa Soal Service S.R.L. Iquitos-2023 - Rojas Mayora, Axel Alexis (2024)
This study hypothesized that the implementation of a new data network at SOAL SERVICE S.R.L. had a positive impact on internal connectivity and communications. The applied methodology, utilizing a quantitative approach and quasi-experimental design, assessed the performance, availability, and regulatory compliance of the network before and after the intervention. The results revealed significant improvements in bandwidth, latency, uptime, and regulatory compliance, supporting the general hypothesis. Implications of these findings are discussed, with additional considerations such as user satisfaction and scalability highlighted. In conclusion, the implementation of the new network proved to be a beneficial investment, enhancing key aspects of the network infrastructure and emphasizing the importance of comprehensive evaluations in technological projects. Suggestions for future research areas include exploring emerging technologies and conducting long-term cost-benefit analyses.